Nonaneurysmal Subarachnoid Hemorrhage Secondary to Transsphenoidal Surgery for Pituitary Adenomas. Issue 2 (March 2015) - Shu, Hansheng; Tian, Xuping; Wang, Hao; Zhang, Hui; Zhang, Qiujian; Guo, Liemei
<x xml:space="preserve">Abstract</x> Abstract Nonaneurysmal subarachnoid hemorrhage (SAH) is a rare and severe complication of transsphenoidal surgery for pituitary adenoma(PA). To improve recognition of this complication, we reviewed and examined 4 patients with nonaneurysmal SAH secondary to transsphenoidal surgery for PAs. Furthermore, possible causes contributed to the SAH, and the attention on preventing the occurrence of SAH is reviewed and stressed.